Cover Picture: Boronate Ligands in Materials: Determining Their Local Environment by Using a Combination of IR/Solid‐State NMR Spectroscopies and DFT Calculations (Chem. Eur. J. 3/2013). Issue 3 (7th January 2013) - Sene, Saad; Reinholdt, Marc; Renaudin, Guillaume; Berthomieu, Dorothée; Zicovich‐Wilson, Claudio M.; Gervais, Christel; Gaveau, Philippe; Bonhomme, Christian; Filinchuk, Yaroslav; Smith, Mark E.; Nedelec, Jean‐Marie; Bégu, Sylvie; et al.
<x xml:space="preserve">Abstract</x> In contrast to boronic acids, RB(OH)2, which have been extensively studied for applications in catalysis and materials chemistry, boronate anions, RB(OH)3−, have drawn much less attention. Their coordination chemistry in the context of alkaline earth metals has only recently been reported. D. Laurencin et al. present an in depth study of a new crystalline phase, calcium butylboronate, in their Full Paper on page 880 ff. A methodology combining high‐resolution solid‐state NMR spectroscopy, IR spectroscopy, and DFT calculations was developed for the analysis of the local structure around boronates in the solid state.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>